2005
DOI: 10.1007/s11172-006-0125-2
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective hydrogenation of levulinic acid esters in the presence of the RuII-BINAP-HCl catalytic system

Abstract: The rate of hydrogenation of γ ketoesters MeCOCH 2 CH 2 COOR (R = Et, Pr i , Bu t ) in the presence of the chiral Ru II -BINAP catalyst (BINAP is 2,2´ bis(diphenylphosphino) 1,1´ binaphthyl) greatly increases upon the addition of 5-10 equivalents of HCl with respect to ruthenium. In the hydrogenation of ethyl levulinate, the optically active γ hydroxy ester ini tially formed would cyclize by ~95% to give γ valerolactone with optical purity of 98-99% ee. When the Ru(COD)(MA) 2 -BINAP-HCl catalytic system is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Catalytic hydrogenation of oxo ester 1 and analysis of the reaction products were carried out as described in the pre ceding paper. 1 Here the catalyst for the asymmetric hydrogena tion and deuteration of oxo ester 1 was prepared in situ without isolating the intermediate complex [((S) BINAP)RuCl 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Catalytic hydrogenation of oxo ester 1 and analysis of the reaction products were carried out as described in the pre ceding paper. 1 Here the catalyst for the asymmetric hydrogena tion and deuteration of oxo ester 1 was prepared in situ without isolating the intermediate complex [((S) BINAP)RuCl 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30][31] In early pioneering studies Osakada et al, [32] showed the activation of C-O bonds of five membered cyclic anhydride, aldehydic and keto acids using two different ruthenium ( [10] demonstrated the use of an in situ generated Ru catalyst using a combination of Ru(acac) 3 and the strongly electron donating phosphine P n Bu 3 in the presence of NH 4 PF 6 for LA hydrogenation to GVL ( [33] reported the effect of the mondentate and chelating phosphines: trioctylphosphine (P n Oct 3 ), 1,4-diphenylphosphinobutane (DPPB) and triphos ( fig. 2) and various acidic additives for the transformation of LA.…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 99%
“…[35,36,53,54] Ru and Ir phosphine complexes have provent ob ee ffective catalysts for CÀOb ond activation in carboxylic acids derivatives. [30][31][32][33] In early pioneering studies, Osakada et al [34] [10] demonstrated the use of an in situ-generated Ru catalyst using ac ombination of [Ru(acac) 3 ]( acac = acetylacetonate) and the strongly electron-donating phosphine PnBu 3 in the presence of NH 4 PF 6 for LA hydrogenation to GVL ( Table 1, entry 3). The reaction demonstrated quantitative conversion of LA to GVL.…”
Section: Hydrogenation Of Levulinic Acid To G-valerolactonementioning
confidence: 99%
See 1 more Smart Citation
“…12 Earlier, we have studied asymmetric catalytic hydro genation of prochiral substrates containing a keto group. [13][14][15][16] In the present work, we made an attempt to use similar approach to the synthesis of chiral δ amino acids starting from available δ keto acids. 5 Oxo 5 phenylpentanoic acid (1) has been chosen as the starting compound (Scheme 1), which gave rise to two model sub strates, viz., ω enamides 4 and 9.…”
mentioning
confidence: 99%